A critical review of insurance claims management: A study of selected insurance companies in Nigeria - Tajudeen Olalekan Yusuf; Sunday Stephen Ajemunigbohun; Gbenga Noah Alli (SPOUDAI - Journal of Economics and Business, 2017)
This study is an empirical investigation of insurance claims management among selected insurance companies in Nigeria. For this purpose, the researchers have been able to review critically the significant contribution of the claims processing in the management of insurance firms' claims. This study conducted in Lagos metropolis, employed a descriptive survey design using random sampling technique and thus gathered data through the use of structured questionnaire. The sample population consisted of 127 respondents made up of claims managers and other members of staff within the surveyed companies. One sample T-test was adopted in the analysis of collected data. Empirical assessment reveal that the various claims handling processing have significant effects in the claims management processes of insurance companies. The findings from study confirm the significance of the various claims handling processing in claims management of insurance companies in Nigeria. It therefore recommends that claims manager should put forward strategic plans to ensuring that insurance claims complaint files are properly kept, monitored and handled for needs that may warrant its usefulness in the future. Also, state-of-the-art training mechanism should be put in place to enhance and improve the working pattern of a claim officer which invariably might affect the organizational efficiency of insurance companies and lastly, Government should harmonize their resources and technical knowhow with the Nigerian insurance industry in ensuring that insurance claims are well designed to curtail fraudulent claims experienced in the past.
Keywords: M04; M19; 330; claims; claims processing; claims management; insurance companies; Nigeria